Optimal power flow with worst-case scenarios considering uncertainties of loads and renewables - Ju, Chengquan (2017)
The growing interest on RES gives traditional power systems an opportunity to evolve towards more sustainable and environmental entities, however the viability of RES would induce stability and reliability issues in power systems. In this paper, a DC optimal power flow (OPF) algorithm considering the worst-case scenario is proposed. It accounts for uncertainties brought by loads and renewable energy sources (RES), while in the meantime the highest reliability level of the system can be achieved. By assigning selected values with largest probabilities to random variables, the probabilistic OPF formulation is converted into a set of deterministic OPF problems in which the additional auxiliary constraints are implemented to represent the uncertain influences. The proposed OPF with the worst-case scenario is applied into an IEEE 14-bus and 57-bus benchmark power system. The results in the simulation along with other OPF techniques shows the validity and robustness of the algorithm.